(untitled) (Botanica Orientalis: Journal of Plant Science, 2025)
Invasion of alien plant species is one of the major drivers that alter ecosystems, and threaten native plant diversity. In this study, we compared the diversity of native and alien plant species (naturalized and invasive) in three forest types in the mid-hills of central Nepal. We selected eight community-managed forests in three districts with similar management practices. Altogether, 24 plots (50 m × 20 m each) were sampled to collect vegetation data. We recorded 274 (88%) native and 24 (8%) alien plant species. The species richness did not vary significantly across the forest types. Among the alien plants, 12 species were naturalized, 11 were invasive including the globally worst species Chromolaena odorata, and the remaining one was casual. Native plant diversity was high in the Pinus roxburghii forest while alien plant diversity was high in the Schima-Castanopsis forest. The Shorea robusta forest with relatively mature trees, low anthropogenic disturbances, and dense canopy cover had the lowest diversity of invasive alien plants followed by Pinus roxburghii and Schima-Castanopsis forests. Contrary to the expectation, there was no significant relationship between canopy cover and species richness of native and alien plant species. Although the three studied forest types did not significantly vary in plant species richness the recorded number of alien species indicates that the community forests of the mid-hills are being invaded rapidly by alien plants. Implementation of appropriate control measures is recommended to reduce the abundance of invasive alien plants in forests and avert likely negative impacts on native species and ecosystems.